Identifikasi Problematika Pelacuran dalam Perspektif Hukum - Indarto Indarto (Humaniora, 2015)
Prostitution is a classic social problem existed continuously as though it is difficult to eradicate. It makes the topic on prostitution becomes interesting to discuss. This paper identified the problem of prostitution from the viewpoint of positive law and empirical reality in society. By combining normative and empirical studies, the article aims to provide an overview of the problem of prostitution more clearly. From the library resarch, it is found various types of prostitution occur. In addition, the motivation to commit prostitution was not solely caused by economic motives, but there were other motives such as drug abuse, for instance. To keep prostitution is not rampant, it is not solely relying on legal instruments, but the role and function of the family is important. Therefore, the problem of prostitution is not simply seen from one point of view, there are other factors as its cause.